Design of reinforced concrete cantilever retaining wall using Grey wolf optimization algorithm. (February 2020) - Kalemci, Elif Nur; İkizler, Sabriye Banu and Dede, Tayfun and Angın, Zekai
Abstract: The purpose of this article to design a low-weight cantilever reinforced concrete retaining wall with shear key by using an optimization algorithm, which is programmed in MATLAB. Grey Wolf Optimization (GWO) is an optimization technique which is developed by mimicking hierarchy and hunting methods of grey wolves. The Retaining Wall was formulated as an optimization problem based on ACI 318–05 code and Rankine's theory for lateral earth pressure. The constrains based on safety factors and design factors were used to reach the best design. The geotechnical constraints were determined as the factor of safety against overturning, bending, bearing capacity failure and the structural constraints were determined as the moment and shear capacities of for elements of the wall. Two numerical examples for optimal design of retaining wall with/without shear key were considered to evaluate the efficiency of GWO algorithm compared to similar studies.